The Effect of Egg White Consumption on the Healing Process of Perineum Wounds - Wigati, Putri Wahyu; Sari, Dewi Kartika (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The slow healing process of perineum wounds can increase the risk of infection, so it is necessary to intake proteins that support the growth of new cells in the perineum wound. This research is based on the high incidence of perineum need with delay in the healing process of perineum wounds in the Kediri Regency. The purpose of this study is to find out the effect of egg white consumption on the healing process of perineum wounds in postpartum mothers. The design used in this study is a Quasi Experiment with Nonequivalent Control Group design. The sampling technique used is purposive sampling. Mann Whitney statistical test results showed that the value of ρ value (0,000) < α (0.05) its means that there is an effect of egg white consumption on the process of welcoming perineum wounds on postpartum mothers.